Reliability Analysis of A Web-Based Expert System Using Forward Chaining for Assessing Diabetic Foot Ulcer Infection Risk - Kharisma Pratama; Syahid Amrullah; Jaka Pradika; Suriadi Jais (Indonesian Journal of Global Health Research, 2025)
A web-based expert system application using the Forward Chaining method has been developed to assist medical professionals in determining the risk scale of diabetic foot infection. Diabetic foot ulcers are a serious complication that requires early detection and accurate risk assessment to prevent further complications such as amputation. The reliability of this application needs to be evaluated to ensure its consistency and dependability in providing medical recommendations. This study aims to analyze the reliability of a web-based expert system application using the Forward Chaining method in determining the risk scale of diabetic foot infection. This research employs a quantitative approach, collecting data from 50 respondents who evaluated four main aspects of the application: Usefulness, Ease of Use, Ease of Learning, and Satisfaction. Reliability analysis was conducted using Cronbach's Alpha with the assistance of SPSS software. The analysis results show a Cronbach's Alpha value of 0.950, indicating that the application has excellent reliability. All four measured aspects are consistent in assessing the application's quality. The web-based expert system application using the Forward Chaining method developed for determining the risk scale of diabetic foot infection has excellent reliability. The application can be relied upon to provide consistent and accurate recommendations in medical risk assessment. A web-based expert system application using the Forward Chaining method has been developed to assist medical professionals in determining the risk scale of diabetic foot infection. Diabetic foot ulcers are a serious complication that requires early detection and accurate risk assessment to prevent further complications such as amputation. The reliability of this application needs to be evaluated to ensure its consistency and dependability in providing medical recommendations. This study aims to analyze the reliability of a web-based expert system application using the Forward Chaining method in determining the risk scale of diabetic foot infection. This research employs a quantitative approach, collecting data from 50 respondents who evaluated four main aspects of the application: Usefulness, Ease of Use, Ease of Learning, and Satisfaction. Reliability analysis was conducted using Cronbach's Alpha with the assistance of SPSS software. The analysis results show a Cronbach's Alpha value of 0.950, indicating that the application has excellent reliability. All four measured aspects are consistent in assessing the application's quality. The web-based expert system application using the Forward Chaining method developed for determining the risk scale of diabetic foot infection has excellent reliability. The application can be relied upon to provide consistent and accurate recommendations in medical risk assessment.